2011
DOI: 10.1124/mol.111.071704
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutagenesis of Aldehyde Dehydrogenase-2 Suggests Three Distinct Pathways of Nitroglycerin Biotransformation

Abstract: To elucidate the mechanism underlying reduction of nitroglycerin (GTN) to nitric oxide (NO) by mitochondrial aldehyde dehydrogenase (ALDH2), we generated mutants of the enzyme lacking the cysteines adjacent to reactive Cys302 (C301S and C303S), the glutamate that participates as a general base in aldehyde oxidation (E268Q) or combinations of these residues. The mutants were characterized regarding acetaldehyde dehydrogenation, GTN-triggered enzyme inactivation, GTN denitration, NO formation, and soluble guanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…This suggests that ALDH3 may be subject to a unique mode of inhibition by GTN that differs from the inhibition of ALDH2. A recent series of studies involving sitedirected mutagenesis experiments led Wenzl et al (2011) to propose three distinct pathways for GTN biotransformation by ALDH2. The dominant pathway involves the formation of nitrite and active site Cys (301 and 303) disulfide formation (Fig.…”
Section: N Nitroglycerinmentioning
confidence: 99%
“…This suggests that ALDH3 may be subject to a unique mode of inhibition by GTN that differs from the inhibition of ALDH2. A recent series of studies involving sitedirected mutagenesis experiments led Wenzl et al (2011) to propose three distinct pathways for GTN biotransformation by ALDH2. The dominant pathway involves the formation of nitrite and active site Cys (301 and 303) disulfide formation (Fig.…”
Section: N Nitroglycerinmentioning
confidence: 99%
“…From an endogenous standpoint, two key roles for ALDHs are the conversion of retinaldehyde to retinoic acid, a metabolic conversion that is involved in the regulation of a host of homeostatic functions, as well as the metabolism of acetaldehyde, a by-product of ethanol metabolism (Stagos et al, 2010;Singh et al, 2013). One of the key xenobiotic roles for ALDH is the bioactivation of nitroglycerin to nitric oxide, resulting in the drug's vasodilatory effects (Chen et al, 2002;Wenzl et al, 2011).…”
Section: Alcohol and Aldehyde Dehydrogenasesmentioning
confidence: 99%
“…This was later confirmed with ALDH2-deficient blood vessels in which the high-affinity pathway of GTN-induced relaxation is absent (Chen et al, 2005). The main route of ALDH2-catalyzed denitration of GTN yields 1,2-glycerol dinitrate (1,2-GDN) and inorganic nitrite, but a minor reaction results in direct formation of NO (Wenzl et al, 2011). Although direct NO formation by ALDH2 observed with the purified enzyme is likely to explain vascular GTN bioactivity, it remains to be shown that this reaction does indeed mediate GTN-induced relaxation of blood vessels.…”
Section: Introductionmentioning
confidence: 58%
“…Esterase activity of ALDH2 (6.6 mg/ml) was measured by monitoring the formation of p-nitrophenolate from p-nitrophenyl acetate (pNPA; 0.1 ALDH2-Catalyzed Bioactivation of GTN Measured as Activation of Purified sGC. Activation of purified sGC (50 ng) by increasing concentrations of GTN (1 nM-440 mM) was determined by incubation of 4 mg of purified ALDH2 at 37°C for 10 minutes in the presence of 0.5 mM [a-32 P]GTP (∼250,000 cpm), 1 mM NAD 1 and 1000 U/ml superoxide dismutase as described previously elsewhere (Wenzl et al, 2009a(Wenzl et al, , 2011Beretta et al, 2010). DPI was present at the indicated concentrations (0.01-100 mM), and DEA/NO (1 mM) served as control for maximal sGC activity.…”
Section: Methodsmentioning
confidence: 99%